A little winning streak: The reptilian‐eye view of gastrulation in birds. (16th November 2012) - Bertocchini, Federica; Alev, Cantas; Nakaya, Yukiko; Sheng, Guojun
<x xml:space="preserve">Abstract</x> The primitive streak is where the mesoderm and definitive endoderm precursor cells ingress from the epiblast during gastrulation. It is often described as an embryological feature common to all amniotes. But such a feature has not been associated with gastrulation in any reptilian species. A parsimonious model would be that the primitive streak evolved independently in the avian and mammalian lineages. Looking beyond the primitive streak, can one find shared features of mesoderm and endoderm formation during amniote gastrulation? Here, we survey the literature on reptilian gastrulation and provide new data on Brachyury RNA and laminin protein expression in gastrula‐stage turtle (Pelodiscus sinensis) embryos. We propose a model to reconcile the primitive streak‐associated gastrulation in birds and the blastopore‐associated gastrulation in extant reptiles.